Memecylon pseudomegacarpum M.Hughes (Melastomataceae), a new species of tree from Peninsular Malaysia - Hughes, Mark (European Journal of Taxonomy, 2013)
A new species, Memecylon pseudomegacarpum (Melastomataceae), is described from southern Peninsular Thailand, Peninsular Malaysia and Singapore. This taxon was previously known under the misapplied name M. megacarpum, which is now considered endemic to Borneo. Memecylon pseudomegacarpum sp. nov. differs from M. megacarpum in having smaller leaves (8–)10.5–17(–22.5) cm rather than (10–)17–28(–35) cm long, with an elliptic lamina (not lanceolate) with a raised mid-rib (not sunken) and a marginal vein which is 2–4 mm from the margin (not 5–12 mm). Both species have similar flowers and share large (c. 15 mm diameter) globose fruits.